Study of Socio-Economics and Infrastructure Gap in Muja Muju Urban Village, Yogyakarta - Ulfah Dwity Jelvi; Adrienne Arsya Haryadi; Bakti Nusantara; Muhammad Fakih Arisandi; Suparwoko; Tri Astuti Ratna Ningsih (Journal of Architectural Research and Design Studies, 2024)
Residential areas are often a reflection of the disparities that exist in society, with some areas experiencing poverty, unequal access to basic services, and limited economic opportunities. The case study taken in this research was in Ledhok Timoho Village in Muja Muju, Yogyakarta. This village faces problems with limited infrastructure, uncertain land ownership, and high levels of socio-economic inequality among its residents. This research discusses the role and participation of the community and government in designing and implementing solutions such as developing green open spaces, poverty alleviation programs, and strengthening local culture and their impact on environmental sustainability and the welfare of the residents of Ledhok Village. This research uses a qualitative method by looking at the socio-economic conditions and conditions in Ledhok Timoho Village and the surrounding area and then linking them to the SDGs. Data obtained using observation and interview methods with local residents in Ledhok Timoho Village. This was done to achieve the aim of this research, namely to identify social disparities that occur between Ledhok Timoho Village and the surrounding area, so the results obtained are that Ledhok Timoho Village and its outer areas had significant differences in various fields such as economic, social, environmental, urban/urban, suburban/suburban, and national, and regional development. Keywords: Economy; Infrastructure; Muja Muju; Social Gap; Sustainable Cities; Yogyakarta